Clinical Outcomes and Long-Term Prognosis in Patients Undergoing Angioplasty - Khan, Farhat Ullah; Khan, Muhammad Idrees; Khan, Qasim Ahmad; Farooq, Umar; Muhammad, Hafeez; Khattak, Imran Qadar (Indus Journal of Bioscience Research, 2024)
Objective: To investigate the influence of lifestyle factors, including smoking, physical activity, and dietary habits, on the severity of coronary artery disease (CAD) in patients without comorbidities and to identifying the prevalence of unhealthy lifestyle habits and exploring their relationship with CAD severity. Methodology: This was a prospective observational cohort study conducted at Hayatabad Medical Complex, Peshawar, from January to June 2022. A total of 200 patients with CAD and no comorbidities were included. Data on lifestyle factors were collected through standardized questionnaires and clinical records. Statistical analyses, including chi-square tests, were applied to assess associations between lifestyle factors and CAD severity. Results: The results indicated that 45% of patients were smokers, 40% were physically inactive, and 53% had unhealthy dietary habits. Despite the prevalence of these risk factors, no statistically significant association was found between smoking status and CAD severity (p > 0.05). However, the cumulative effect of unhealthy lifestyle factors was evident, with higher CAD severity noted in patients exhibiting multiple risk factors. Conclusion: The study highlights the significant impact of lifestyle factors on CAD outcomes, reinforcing the need for public health interventions targeting smoking cessation, physical activity, and dietary improvements. Effective lifestyle modifications can potentially reduce the progression of CAD in the local population.